1993
DOI: 10.1021/bi00096a006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of kanamycin nucleotidyltransferase determined to 3.0-.ANG. resolution

Abstract: Kanamycin nucleotidyltransferase, as originally isolated from Staphylococcus aureus, inactivates the antibiotic kanamycin by catalyzing the transfer of a nucleotidyl group from nucleoside triphosphates such as ATP to the 4'-hydroxyl group of the aminoglycoside. The molecular structure of the enzyme described here was determined by X-ray crystallographic analysis to a resolution of 3.0 A. Crystals employed in the investigation belonged to the space group P4(3)2(1)2 with unit cell dimensions of a = b = 78.9 A an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 56 publications
7
61
0
Order By: Relevance
“…All substitutions at G93, G94, and D107, except G94L, also caused almost complete loss of UTase activity under both conditions. These data confirm an important role for these NT domain residues in UTase activity, as predicted by the structural analysis of this domain from other family members (17,18,58,62,65). Importantly, the HD substitution mutants (HD-AA and HD-QN) shown above to lack UR activity (Fig.…”
Section: Fig 2 Modification Of Glnb In Rsupporting
confidence: 83%
See 2 more Smart Citations
“…All substitutions at G93, G94, and D107, except G94L, also caused almost complete loss of UTase activity under both conditions. These data confirm an important role for these NT domain residues in UTase activity, as predicted by the structural analysis of this domain from other family members (17,18,58,62,65). Importantly, the HD substitution mutants (HD-AA and HD-QN) shown above to lack UR activity (Fig.…”
Section: Fig 2 Modification Of Glnb In Rsupporting
confidence: 83%
“…The structures of this domain have been solved for several family members and are very similar to each other (17,18,27,50,58,59,65,73). These structures also show that the two conserved aspartate residues (aspartate and glutamate residues in some members) are involved in the direct or indirect binding of metal ions, which are essential for substrate catalysis (18,62,65). In kanamycin nucleotidyltransferase (Kan-NT) and DNA polymerase ␤, conserved glycine and serine residues are located in the helical-turn motif, connecting the first ␤-sheet and a short helix.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Crystal structures for four aminoglycoside-modifying enzymes have been reported (21,36,42,53,56). These are for ANT(4Ј), AAC(3), AAC(6Ј), and APH(3Ј) type IIIa [APH(3Ј)-IIIa].…”
Section: Resistance To Aminoglycosides and Strategies To Counter Itmentioning
confidence: 99%
“…The apparent difference between the model of the rabbit liver enzyme and the model of the S. shibatae enzyme raises the question of the relatedness of these two enzymes+ Sequence analysis of CCA-adding enzymes indeed has separated the archaeal enzymes as class I from the eucaryotic and eubacterial enzymes as class II (Yue et al+, 1996)+ All of these enzymes are members of the family of nucleotidyltransferases, which also includes poly(A) polymerase, terminal deoxynucleotidyltransferase, DNA polymerase b, and kanamycin nucleotidyltransferase (Holm & Sander, 1995;Martin & Keller, 1996)+ The crystal structures of DNA polymerase b and kanamycin nucleotidyltransferase are known, and analysis of these structures shows a conserved DXD motif at the catalytic site (Sakon et al+, 1993;Davies et al+, 1994;Sawaya et al+, 1994)+ The class I members of the nucleotidyltransferase family share the conserved DXD motif, but lack major homology (Yue et al+, 1996)+ The class II members, in contrast, share a more extensive homology in the N-terminal domain that contains the DXD motif (Shanmugam et al+, 1996)+ In both classes, the CCA-adding enzymes are most closely related to poly(A) polymerase in sequence (Masters et al+, 1990;Cao & Sarkar, 1992;He et al+, 1993)+ To gain further insights into the separation of the two classes and to determine if this separation is the basis for the distinct features between the rabbit liver model and the S. shibatae model, the examination of an eubacterial CCA-adding enzyme would be important+ This study focused on the E. coli CCA-adding enzyme as an example of the eubacterial enzymes and aimed to gain insights in two directions+ First, as the E. coli enzyme partitions in the alignment with the eucaryotic enzymes, it provided an independent test of the two models+ Second, mutant tRNAs that have altered 39 ends have been isolated (O'Connor et al+, 1993), such as E. coli tRNA Val variants ending with GCA, ACA, and Salmonella typhimurium tRNA His variants ending with UCA+ The study of the E. coli enzyme could shed light on the origin of these natural variations+ Recent studies of the E. coli enzyme showed that it efficiently recognized synthetic minihelices that consist of just the acceptor and T⌿C stems of a full-length tRNA (Shi et al+, 1998b)+ This provided the rationale to use minihelices as substrates to examine enzyme specificity at each of the 74-76 positions+ Minihelices were prepared chemically to ensure a clearly defined 39 end+ Results here showed that the E. coli CCA-adding enzyme catalyzed aberrant synthesis of 39 ends both to minihelices and to a reconstituted tRNA+ In the absence of ATP, the enzyme synthesized 39 ends of C, CC, CCC, or poly(C) as if it were a poly(C) polymerase+ Addition of ATP had a regulatory effect+ It abolished the synthesis of CCC and inhibited the synthesis of poly(C)+ The poly(C) polymerase activity and the regulatory role of ATP led to a model of the untemplated synthesis of CCA+ This model sheds light on the separation of two classes of the CCA-adding enzymes in evolution and their close sequence relationship with po...…”
Section: Introductionmentioning
confidence: 99%